Analisis Disiplin Kerja, Komunikasi Interpersonal, dan Kepemimpinan Terhadap Kinerja Pegawai Badan Penanggulangan Bencana Daerah Provinsi Sumatera Utara - Fitri, Uci Aulia; Saragih, Megasari Gusandra; Darmilisani, Darmilisani (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of the research is to determine the effect of work discipline, interpersonal communication, and leadership on the performance of employees at the Regional Disaster Management Agency of North Sumatra Province. This study uses multiple linear regression analysis. Primary data collection was conducted using a questionnaire. The data method used is quantitative with the assistance of SPSS version 27. The sample in this study consisted of 64 respondents. The results of the test for the work discipline variable indicate that work discipline has a positive and significant effect on employee performance partially. The results of the test for the interpersonal communication variable indicate that interpersonal communication has a positive and significant effect on employee performance partially. The test results for the leadership variable show that leadership has a positive and significant effect on employee performance. The simultaneous test results indicate an F-value of 105.238 and a significance value of 0.000, which is less than 0.05, thus it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected, meaning that work discipline, interpersonal communication, and leadership have a significant simultaneous effect on the performance of employees of the regional disaster management agency of North Sumatra province